ANALISIS HUBUNGAN AKREDITASI SEKOLAH LUAR BIASA DENGAN MUTU PENDIDIKAN DI SLB-C NEGERI PEMBINA PROVINSI KALIMANTAN SELATAN - Muhammad Firdaus Nuzula; Aslamiah , Aslamiah; Celia Cinantya (Journal of Innovation Research and Knowledge, 2024)
Education is an important element that aims to educate and develop individual potential. Through education, a person can build creativity, broaden their horizons, and develop a good personality. The quality of education in schools varies, which is largely influenced by the school's accreditation. Accreditation can be defined as formal recognition given by an authorized body to a school as an educational institution, indicating the suitability and quality of the school. High accreditation is usually associated with good quality education, reflects the quality of the institution and increases public trust in the school. However, in practice, accreditation is often viewed as a formal status without understanding its substantive meaning as a guarantee of educational quality. This research aims to analyze the relationship between school accreditation and the quality of education in SLB-C Negeri Pembina, South Kalimantan Province. Guaranteeing the quality of education through accreditation aims to ensure that students receive educational services and results that meet the promised standards. This research also aims to identify the extent to which accreditation at SLB reflects the actual quality of education, as well as its role in providing quality assurance to the community and education stakeholders.